Application of (Ca1-xSrx)LaGa3S6O:Eu2+ phosphor in white light-emitting fabrication - Dieu An Nguyen Thi; Phan Xuan Le (Institute of Advanced Engineering and Science, 2022)
An alternating sequence of Ca1-xSrxLaGa3S6O:0.05Eu2+ phosphors was produced using high-thermal and solid-state reactions. It has outstanding excitations at the range between 350 and 500 nm suitable for the close-ultraviolet or GaN-based blue LED chips. These phosphor peaks have a blue shift between 560 and 540 nm when the Sr concentration (x) rises. The Sr content (x) can be modified to produce an illumination with a color between yellow and green. As a result, we can conclude that solid solutions Ca1-xSrxLaGa3S6O:0.05Eu2+ are excellent for use in manufacturing white LEDs. Our data may become valuable for producers in the task of making white light emitting diode (WLED) devices suitable for them.